Penegakan Hukum oleh Penyidik Satreskrim Kepolisian Resort Limapuluh Kota Terhadap Tindak Pidana Peredaran Rokok Ilegal - Anton Luter; Ismansyah Ismansyah; Susi Delmiati (UNES Law Review, 2023)
Cases of distribution of goods, especially illegal cigarettes, which are rife in Limapuluh Kota Regency, must be a serious concern. A very significant spike was found in cases resulting from prosecution during the 2019 to 2020 period where the number of illegal cigarettes of various brands destroyed was 4,180,352 (four million one hundred eighty thousand three hundred and fifty two) cigarettes. This research is legal research with descriptive analytical research specifications. The approach used is a normative juridical approach, supported by an empirical juridical approach. The data used is secondary data as main data and primary data as supporting data, which was collected through literature study/document study and field study using interview techniques. The data was then analyzed qualitatively and presented in analytical descriptive form. Based on the results of research, discussion and analysis, the following conclusions can be drawn: First, law enforcement at the level of investigating criminal acts of distribution of illegal cigarettes at the Fifty Cities Police Criminal Investigation Unit by applying the provisions of Article 199 in conjunction with Article 114 of Law Number 36 of 2009 concerning Health in conjunction with Article 62 Paragraph ( 1) Juncto Article 8 Paragraph (1) Letter I of Law Number 8 of 1999 concerning consumer protection Juncto Article 55, Article 56 of the Criminal Code. Second, the obstacles faced by the Limapuluh Kota Resort Police Criminal Investigation Unit in enforcing the law against the criminal act of distributing illegal cigarettes are the lack of personnel, lack of community role and the difficulty of finding illegal cigarette distributors. Third, the efforts made by the Limapuluh Kota Resort Police Criminal Investigation Unit in enforcing the law against the criminal act of distributing illegal cigarettes are by conducting examinations of health experts, conducting examinations of criminal experts and conducting examinations of witnesses of PT Leadon Tobacco, which is a factory that produces Luffman brand cigarettes.